THE GALANG BATANG AGREEMENT IN THE RESOLUTION OF MARITAL CONFLICTS IN GUNUNG MANAON 1 VILLAGE: AN ISLAMIC LEGAL PERSPECTIVE - Lily Dahreni Siregar; Fatimah Fatimah (Journal Analytica Islamica, 2025)
This study examines the Galang Batang agreement as a form of conflict resolution between husband and wife in Gunung Manaon 1 Village from the perspective of Islamic law. Galang Batang is a local customary practice that serves as an informal mediation method in resolving marital disputes. The aim of this study is to understand the implementation mechanism of the Galang Batang agreement, its effectiveness in preserving household harmony, and the extent to which this practice aligns with Islamic legal principles, particularly in terms of justice, public interest (maslahah), and family dispute resolution. This research employs a qualitative method with a normative-sociological approach, through interviews with traditional leaders, married couples, and local religious figures. The findings reveal that Galang Batang not only functions as a means of conflict resolution but also reinforces social and religious values. From the perspective of Islamic law, this practice is acceptable as long as it does not contradict the sharia and upholds the principles of consultation (shura), justice, and peace. Therefore, Galang Batang represents a form of harmonization between customary law and Islamic law in resolving family conflicts.